THE ROLE OF FIRM SIZE IN MODERATING THE RELATIONSHIP BETWEEN PROFITABILITY AND FIRM VALUE: Firm Value, Firm Size, Profitability - Inrawan, Ady; Silitonga, Hery Pandapotan; Dermawan Sembiring, Lenny (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
The primary objective of this study is to analyze the effect of profitability on firm value, with firm size serving as the moderating variable. The data used in this study are secondary data in the form of financial statements obtained from the Indonesia Stock Exchange (IDX) and the websites of the sampled companies. The research population consists of 27 companies in the heavy constructions & civil engineering subsector during the 2019–2023 period. Using a purposive sampling method, 17 companies were selected, resulting in 85 observations. The data analysis technique employed is multiple linear regression with a moderating variable (Moderated Regression Analysis/MRA). The analysis was conducted using panel data with EViews 13 software. Model selection was performed using the Chow Test, Hausman Test, and Lagrange Multiplier Test. The results indicate that profitability does not significantly affect firm value. However, firm size is proven to moderate the relationship between profitability and firm value, although the moderation coefficient demonstrates a negative effect. This suggests that larger firms face managerial complexity challenges that may actually weaken the influence of profitability on firm value. This study is expected to serve as a reference for corporate management and investors in considering the influence of profitability and firm size on firm value